READING QURAISH SHIHAB'S ORAL EXEGESIS ABOUT GLORIFYING WOMEN IN SOCIAL MEDIA - M. Riyan Hidayat; Ahmad Murtaza MZ (International Conference on Social and Islamic Studies, 2021)
This paper will explain the oral interpretation of Quraish Shihab about glorifying women on social media on the Shihab N Shihab program which is monitored by one of his daughters, Najwa Shihab. The description will explain in the form of a descriptive analysis approach. The data is collected from recorded social media documentation and literature studies. Meanwhile, the theory that will be used in this research is the theory of oral exegesis, which was initiated by Andreas Gorke. The author concludes that the oral practice developed by Quraish Shihab has two faces, namely the context in the Qur'an and the hadith, while the second is the context outside the text of the Qur'an and hadith which is more social in society.